Art and religious reform in early modern Europe - Heal, Bridget; Koerner, Joseph Leo (Art history book series, 2018)
"The religious turmoil of the sixteenth century constituted a turning point in the history of Western Christian art. The essays presented in this volume investigate the ways in which both Protestant and Catholic reform stimulated the production of religious images, drawing on examples from across Europe and beyond"--